Idiopathic noncirrhotic portal hypertension: current perspectives - Riggio O (Dove Medical Press, 2016)
Oliviero Riggio,1 Stefania Gioia,1 Ilaria Pentassuglio,1 Valeria Nicoletti,1 Michele Valente,2 Giulia d’Amati2 1Department of Clinical Medicine, Center for the Diagnosis and Treatment of Portal Hypertension, 2Department of Radiological, Oncological, and Pathological Sciences, Sapienza University of Rome, Rome, Italy Abstract: The term idiopathic noncirrhotic portal hypertension (INCPH) has been recently proposed to replace terms, such as hepatoportal sclerosis, idiopathic portal hypertension, incomplete septal cirrhosis, and nodular regenerative hyperplasia, used to describe patients with a hepatic presinusoidal cause of portal hypertension of unknown etiology, characterized by features of portal hypertension (esophageal varices, nonmalignant ascites, porto-venous collaterals), splenomegaly, patent portal, and hepatic veins and no clinical and histological signs of cirrhosis. Physicians should learn to look for this condition in a number of clinical settings, including cryptogenic cirrhosis, a disease known to be associated with INCPH, drug administration, and even chronic alterations in liver function tests. Once INCPH is clinically suspected, liver histology becomes mandatory for the correct diagnosis. However, pathologists should be familiar with the histological features of INCPH, especially in cases in which histology is not only requested to exclude liver cirrhosis. Keywords: idiopathic portal hypertension, obliterative portal venopathy, esophageal varices, splenomegaly